Peranan Kuliah Kerja Nyata di TK Islam Bani Qiroat Pola Asuh Anak untuk Membangun Tumbuh kembang Anak di Era Digital - Muhamad Heru Adriansyah; Nada Bela; Ibnu Adham; Asep Hermawan; Lisa Ariani Lutfi (Universitas Pahlawan Tuanku Tambusai, 2026)
Community Service Program (KKN) is a form of student community service as part of the implementation of Universitas Tangerang Raya. The development of digital technology brings both opportunities and challenges to early childhood parenting. The KKN, as a forum for student service, has the potential to help families and PAUD/TK institutions build parenting patterns that are conducive to child development in the digital era. KKN activities at Bani Qiroat Islamic Kindergarten include mentoring parents on children's digital literacy, teacher training on integrating age-appropriate technology-based educational games, and a workshop on setting limits on device use (screen time). This report presents the approach, implementation, qualitative findings, and recommendations for parenting practices that are responsive to digital challenges. The results of the evaluation of the practices indicate an increase in parents' and teachers' understanding of parenting principles that support children's cognitive, emotional, and social development in the digital era.